An examination of the relationship between cultural competence, self-efficacy, and cultural knowledge - Arikan, Rahmi A. (My University, 2019)
This study examined the relationship between self-efficacy, cultural competence and cultural knowledge and confidence. Participants (N = 398) completed a survey that included items focused on self-efficacy, cultural competence, and cultural knowledge and confidence in that knowledge. The results indicated that self-efficacy did not predict a significant amount of variance in terms of cultural knowledge, knowledge confidence or overall cultural competence. However, a significant relationship was observed between cultural competence and confidence in cultural knowledge, as participants' average cultural competence scores predicted 19% of the variance in participants' confidence ratings in their performance on a cultural knowledge inventory. It was predicted that participants in this study would potentially demonstrate a Dunning-Kruger effect, and this prediction was supported by a significant interaction between performance in general cultural knowledge and confidence in that knowledge. Specifically, participants were assigned to quartiles based on their mean cultural knowledge percentage score, and confidence percentages were compared to knowledge percentages for the four quartiles. Specifically, participants in the 2nd and 3rd quartiles demonstrated accurate alignment in their answer and confidence responses, while participants in the bottom quartile reported significant overconfidence in their knowledge and participants in the top quartile demonstrated significant under-confidence in their answer accuracy.
Keywords: Cultural competence; Self-efficacy; Culture